The application of the Exodus divine-presence narratives as a biblical socio-ethical paradigm for the contemporary redeemed - Le Roux, J.H. (Jurie Hendrik), 1944- (University of Pretoria, 2013)
Thesis (PhD)--University of Pretoria, 2011.